The endangered self : managing the social risk of HIV - Green, Gill, 1956-; Sobo, Elisa Janine, 1963- (Routledge, 2000)
"To date, the majority of HIV/AIDS research has concentrated on education and prevention for those with a seronegative status, and studies of HIV positive individuals have been concerned with their potential to infect others. The Endangered Self, however, focuses on how the discovery of an HIV-positive status affects the individual's sense of identity and on the experience of living with HIV, and its effects on the individual's social relationships." "Drawing upon the concepts of stigma, dangerous identities, and health risk, the authors describe the revaluation that people living with HIV and AIDS must make of the risks entailed by everyday social interactions, and examine their negotiation of these interactions. In this study, which combines a UK/US perspective, Green and Sobo explore identity change and the stigma attached to an HIV-positive status within the context of the sociology of risk."--Jacket.
Keywords: AIDS (Disease) -- Social aspects.; AIDS (Disease) -- Psychological aspects.; Patients.; Immunologic diseases.; Human behavior.; Sexually transmitted diseases.; Public health.; Retrovirus infections.; Virus diseases.; Statistics.; Health services administration.; Diseases.; Medical care.; Risk assessment.; Group identity.; Social adjustment.; HIV infections.; Lentivirus infections.; Risk management.; Probabilities.; Victims.; Risk.; Immunological deficiency syndromes.; Organization.; Patients; Immune System Diseases; Behavior; Sexually Transmitted Diseases; Public Health; Retroviridae Infections; Persons; Virus Diseases; Statistics as Topic; Behavior and Behavior Mechanisms; Environment and Public Health; Health Services Administration; RNA Virus Infections; Named Groups; Disease; Health Care Evaluation Mechanisms; Delivery of Health Care; Psychiatry and Psychology; Risk Assessment; Social Identification; HIV Long-Term Survivors; Social Adjustment; HIV Infections; Epidemiologic Methods; Investigative Techniques; Quality of Health Care; Health Care Quality, Access, and Evaluation; Analytical, Diagnostic and Therapeutic Techniques and Equipment; Lentivirus Infections; Risk Management; Sexually Transmitted Diseases, Viral; Epidemiologic Measurements; Probability; Survivors; Social Behavior; Risk; Immunologic Deficiency Syndromes; Organization and Administration; HIV Infections -- psychology; HIV Long-Term Survivors -- psychology; Patient Care; Sida -- Aspect social.; Sida -- Aspect psychologique.; Maladies immunologiques.; Comportement humain.; Infections transmissibles sexuellement.; Santé publique.; Infections à rétrovirus.; Maladies à virus.; Statistiques.; Services de santé -- Administration.; Maladies.; Prestation de soins.; Évaluation du risque.; Identité collective.; Adaptation sociale.; Infections à VIH.; Infections à lentivirus.; Gestion du risque.; Probabilités.; Victimes.; Risque.; Syndromes de déficit immunitaire.; Organisation.; Statistique.; Soins médicaux.; patients.; human behavior.; public health.; risk assessment.; group identity.; risk management.; probability.; statistics.; MEDICAL -- Long-Term Care.; MEDICAL -- Nursing Home Care.